Effect of adding stretching to standardized procedures on cervical range of motion, pain, and disability in patients with non-specific mechanical neck pain: A randomized clinical trial. Issue 3 (July 2020) - Alfawaz, Saad; Lohman, Everett; Alameri, Mansoor; Daher, Noha; Jaber, Hatem
Abstract: Objective: to investigate the benefit of adding stretching exercises to cervical joint mobilization and active rotation exercises for patients with non-specific mechanical neck pain. Methods: Thirty-eight subjects with non-specific mechanical neck pain were randomly assigned to a standard procedure group (passive cervical mobilization and active cervical rotation range of motion exercise) or a combined procedure (passive cervical mobilization, active cervical rotation range of motion exercises, and stretching procedures). Mixed factorial analysis of variance was used to compare changes between groups over time in active cervical range of motion, Numeric Pain Rating Scale, Neck Disability Index, Global Rating of Change, and Pressure Pain Threshold. Results: There was a significant change in mean active range of motion in all directions, Pressure Pain Threshold, perceived pain, disability levels, and global rating of change over time (p < 0.001). There was a significant group by time interaction in mean active range of motion during extension (p = 0.01), right rotation (p = 0.004), right and left lateral flexion (p = 0.05, and p = 0.02 respectively). However, there was no significant group by time interaction in mean active range of motion during flexion, left rotation, pain intensity (p = 0.09), right and left pressure pain threshold (p = 0.30, 0.47, respectively), and disability (p = 0.07). Conclusions: Both study groups improved significantly in all subjective and objective outcome measures. However, data from this study suggest that adding stretching to the standard procedures may be more effective than the standard procedure alone at improving cervical extension, right rotation, and lateral flexion active range of motion, but not pain and disability.